All Scientists Should Write Poetry: Creative Writing as Essential Academic Practice - Mariya Deykute (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
Creative writing in undergraduate academics has often been regarded as an elective practice that has benefits primarily for students who plan to pursue creative or literary majors. However, poetic inquiry specifically offers crucial benefits to STEM students, owing both to the transformative nature of poetic process and to the way poetic inquiry can stimulate innovative, ethical, multilingual and interdisciplinary growth. The author frames the issue through individual experience of teaching poetry to STEM undergraduates in the context of a rich multilingual environment, in which many students are fluent or proficient in several languages. The author argues that due to the commonalities poetry writing shares with the scientific process, as well as the essential skills it requires of the practitioners, poetry writing is an essential techne in academia rather than a “quirky elective.”
Keywords: JAEPL